SPIRITUAL DEVELOPMENT AS A NECESSARY CONDITION OF WAY OUT OF THE CRISIS FOR SOCIETY - Svitlana Repetii ("Scientific Information Agency "Science-technologies-information" LLC, 2021)
The crisis of the present day, which covered almost all types of life activities, contributes to the development of impoverishment, degradation, leads to an increase of criminality, generates fear, emotional instability in the society. Forced isolation, threat of loss of work and value orientations contribute to the emergence of mental illnesses. Each person is responsible for his actions, thoughts and feelings - for themselves and society. Spiritual development is interpreted as a conscious life activity, transformation of negative qualities, which is considered as a daily inner action. This kind of life activity contributes to the development of unconditioned love, which we interpret as perception of a human being in its entirety without condemnation and pretensions.